The Adaxial/Abaxial Patterning of Auxin and Auxin Gene in Leaf Veins Functions in Leafy Head Formation of Chinese Cabbage - Yue, Xiaozhen; Su, Tongbing; Xin, Xiaoyun; Li, Peirong; Wang, Weihong; Yu, Yangjun; Zhang, Deshuang; Zhao, Xiuyun; Wang, Jiao; Sun, Liling; Jin, Guihua; Yu, Shuancang; et al. (Frontiers in Plant Science, 2022)
Leaf curling is an essential prerequisite for the formation of leafy heads in Chinese cabbage. However, the part or tissue that determines leaf curvature remains largely unclear. In this study, we first introduced the auxin-responsive marker DR5::GUS into the Chinese cabbage genome and visualized its expression during the farming season. We demonstrated that auxin response is adaxially/abaxially distributed in leaf veins. Together with the fact that leaf veins occupy considerable proportions of the Chinese cabbage leaf, we propose that leaf veins play a crucial supporting role as a framework for heading. Then, by combining analyses of QTL mapping and a time-course transcriptome from heading Chinese cabbage and non-heading pak choi during the farming season, we identified the auxin-related gene BrPIN5 as a strong candidate for leafy head formation. PIN5 displays an adaxial/abaxial expression pattern in leaf veins, similar to that of DR5::GUS, revealing an involvement of BrPIN5 in leafy head development. The association of BrPIN5 function with heading was further confirmed by its haplo-specificity to heading individuals in both a natural population and two segregating populations. We thus conclude that the adaxial/abaxial patterning of auxin and auxin genes in leaf veins functions in the formation of the leafy head in Chinese cabbage.